Validation of a mechanistic model for predicting fruit scab infection on different loquat cultivars - Elisa GONZÁLEZ-DOMÍNGUEZ; Vittorio ROSSI; Vittorio FARINA; Giuseppe GIANGUZZI; Mónica BERBEGAL; Josep ARMENGOL (Phytopathologia Mediterranea, 2018)
Scab, caused by Fusicladium eriobotryae, is the main disease affecting loquat (Eriobotrya japonica) in the Mediterranean basin. A mechanistic epidemiological model developed in Spain to predict infection of loquat fruit by conidia was assessed in the main loquat cultivated area of Italy (Sicily). A 3-year study (2014–2016) was carried out in an experimental orchard on three loquat cultivars: Algerie, Peluche and San Filipparo. For each cultivar, output of the model was compared with observed scab development on fruits. The scab epidemics observed were different in different years and cultivars, representing a suitable data set for model validation. The model correctly predicted loquat scab, as demonstrated by the goodness of fit between model predictions and observed disease incidence on fruits (R2 > 0.85), confirming the accuracy and robustness of the model for predicting scab development in loquat orchards. The use of the model for fungicide scheduling against F. eriobotryae may improve the management of loquat scab by reducing the number of required fungicide applications.